Analysis of Factors Related to Nurse Performance in Inpatient Wards Citra Medika General Hospital - Putri, Dwiana Kartika; Tampubolon, Ida Lestari (Jurnal Kesmas Prima Indonesia, 2025)
Introduction:A hospital is a health service organization that is very important for the community. One of the most important resources in determining the success of hospital services is the health workforce. Nurses are one of the professional health workers who provide nursing care to patients whose performance greatly affects the quality of services provided. The performance of a health worker is greatly influenced by several factors that influence a person to continue to improve, direct and maintain their behavior both directly and indirectly with the work environment. Purpose: This study aims to analyze factors related to nurse performance. Method: This research method is quantitative withThe analytical survey research design uses a cross-sectional approach, namely research that tries to explore how and why the phenomenon occurs and then carries out a dynamic analysis of the correlation between the phenomena, both between the independent variables and the dependent variables., the population was 53 nurses in the inpatient room and the sample used was a total sampling of 53 nurses in the inpatient room. The data collection technique used a measuring instrument in the form of a questionnaire. Results: The results of the study showed that the variables of job promotion with a ρ value (0.033), the work itself with a ρ value (0.030) and awards with a ρ value (0.005) had a relationship with nurse performance because the valueρ value< 0.05. Conclusion: Promotion, the work itself, and rewards are related to nurse performance at Citra Medika Hospital.